The essence and structure of the competence of general secondary education teachers in the field of intellectual property - Kravchuk, N. (Problems of Engineer-Pedagogical Education, 2020)
The paper deals with topical issues concerning the protection of the rights of employees of the general secondary education level to their own innovative scientific and methodological works in the field of intellectual property. The works of scientists on this issue are analyzed, relevant national and foreign legal acts regulating the protection of the rights of teachers in the research field are identified. The paper analyses materials on the issues of developing teachers’ professional competence (from the point of view of professional development of a specialist during the process of advanced training) and substantiates the necessity of forming a particular competence in the field of intellectual property within general professional competence, which is aimed at solving situational tasks in the realm of the teachers’ copyright protection. The paper pays particular attention to the substantive content of competences in the field of intellectual property, and considers systemic, basic, parametric and spiral competence models. Competent experience is highlighted as the most important component in solving applied problems in the industry, which, based on the time factor, allows a person to gradually increase the variability of professional decisions regarding intellectual property protection. Specific competence-oriented tasks and situational tasks in the field of intellectual property arising in the course of teachers’ creative professional activity are considered. The necessity of gradual formation of general secondary education teachers’ competence in the field of intellectual property is emphasized (five stages are distinguished, starting from theoretical readiness and ending with practical application of their own acquired competent experience and acquired knowledge in the research field). The necessity of setting specific competence-oriented and situational tasks in the field of intellectual property protection in order to motivate educators, setting specific competence goals and gaining qualitative experience is highlighted separately. The need to develop a technology for the formation of competence in the field of intellectual property is emphasized.